Phase formation during reduction of iron sand with soda ash flux addition - , Pramusanto; Purwanto, Hadi; Dahlan, Yuhelda; Saleh, Nuryadi (Trans Tech Publications Ltd., Switzerland, 2011)
Iron sand deposit in Indonesia generally consisted of titanomagnetite with ilmenite lamelaa occurred in magnetite particle structure, therefore direct physical separation through magnetic method at particle size of 400 mesh only capable increasing total iron content up to 60%. In order to increase the grade of iron, decreasing TiO2 content in iron sand was applied by chemical method of alkaline fusion followed by grinding to 100 mesh and magnetic separation. Pre-oxidation was conducted prior to reduction and alkaline flux was added to coal based reduction system of in a rotary kiln. The alkali addition into the reduction system resulted to the formation of metallic iron and non metallic phases, in which sodium titanate compounds as nonmagnetic product can be separated from calcine using separator magnetic. XRD analyses of the concentrate and tailing as magnetic separation products showed concentrate was dominated by metallic phase compared to oxide phase and it doesn’t consisted iron-titan oxide and iron oxide. On the other hand, tailing was consisted iron-titan oxide and iron oxide.